Kepemimpinan transformasional sebagai kunci peningkatan kinerja guru dan mutu sekolah - Syah, Syahrial; Supiani (Jurnal Pendidik Indonesia, 2024)
This research aims to explore the influence of the principal's transformational leadership on teacher performance and school quality. With a quantitative descriptive approach, a survey was used as a data collection instrument involving teachers in several junior high schools in Meranti Islands Regency. Data analysis used SPSS version 24 to test validity, reliability and carry out multiple linear regression analysis. The research results show that the principal's transformational leadership has a significant influence on teacher performance and school quality, with a contribution of 51.4%, while 48.6% is influenced by other variables. This research fills the gap in the literature regarding the application of transformational leadership in the context of Indonesian schools. These findings provide new insight into the importance of inspirational and inclusive transformational leadership in improving the quality of education. The novelty of the research lies in the holistic and contextual approach, as well as in-depth empirical analysis regarding its implementation. The research also identified concrete strategies for school principals to improve teacher competency and educational quality. These findings are relevant for policy makers and educational practitioners in developing strategies to improve the quality of education.